2010
DOI: 10.1186/1758-5996-2-44
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy in hypertension: An update

Abstract: Meticulous control of blood pressure is required in patients with hypertension to produce the maximum reduction in clinical cardiovascular end points, especially in patients with comorbidities like diabetes mellitus where more aggressive blood pressure lowering might be beneficial. Recent clinical trials suggest that the approach of using monotherapy for the control of hypertension is not likely to be successful in most patients. Combination therapy may be theoretically favored by the fact that multiple factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 73 publications
1
59
0
3
Order By: Relevance
“…In a previous study, in ACE inhibitors with CCBs Cardiovascular Events Trial in patients with hypertension and diabetes, it was found that those receiving this combination were approximately 50% less likely to experience a major cardiovascular event. 7 However, a study conducted in Canada shows that the primary combination includes an ACE inhibitor and diuretic (78%), followed by an ARB and diuretic (16%), and an ACE inhibitor and CCB (6%). 4 About 67% of respondents were given a combination of 3 drugs which comprises of ACE inhibitor, CCB and diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, in ACE inhibitors with CCBs Cardiovascular Events Trial in patients with hypertension and diabetes, it was found that those receiving this combination were approximately 50% less likely to experience a major cardiovascular event. 7 However, a study conducted in Canada shows that the primary combination includes an ACE inhibitor and diuretic (78%), followed by an ARB and diuretic (16%), and an ACE inhibitor and CCB (6%). 4 About 67% of respondents were given a combination of 3 drugs which comprises of ACE inhibitor, CCB and diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly combination therapy was used in our study when compared with the monotherapy which was in accordance with earlier studies. 6,7 Combinations of anti-hypertensive drugs with complementary actions may minimize adverse effects and reduce clinical outcomes by improving BP control and organ protection. 7 Most commonly a combination of 3 drugs was prescribed and amidst various drugs prescribed a CCB (Amlodipine) was the most commonly prescribed drug as it is recommended in older age group and also for chronic use.The most common drug prescribed is comparable to study done by Datta S et al and Almas A et al, although few studies have also shown differing results.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Combinations of anti-hypertensive drugs with complementary actions may minimize adverse effects and reduce clinical outcomes by improving BP control and organ protection. 7 Most commonly a combination of 3 drugs was prescribed and amidst various drugs prescribed a CCB (Amlodipine) was the most commonly prescribed drug as it is recommended in older age group and also for chronic use.The most common drug prescribed is comparable to study done by Datta S et al and Almas A et al, although few studies have also shown differing results. [8][9][10][11] We also found that 70% of the drugs were prescribed from Essential drug list 2011 implying that there was no drug procurement problem and though only 16.67% patients were prescribed generic drugs but still these should be prescribed more often so that the patients can get the options of choosing drug according to his economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that lowering of blood pressure can effectively reduce the risk of cardiovascular events and stroke, but finding the most appropriate therapy is often difficult (1). Combinational therapies employing an angiotensin-converting enzyme inhibitor (ACEi) and indapamide (IND) offer the advantage of using two highly effective agents, increasing both clinical efficiency and patient compliance (2)(3)(4). Low dose combinations of ACEis and diuretics have shown greater reduction in blood pressure and higher success rates in managing hypertension than either of the treatments alone (4)(5)(6).…”
mentioning
confidence: 99%
“…Combinational therapies employing an angiotensin-converting enzyme inhibitor (ACEi) and indapamide (IND) offer the advantage of using two highly effective agents, increasing both clinical efficiency and patient compliance (2)(3)(4). Low dose combinations of ACEis and diuretics have shown greater reduction in blood pressure and higher success rates in managing hypertension than either of the treatments alone (4)(5)(6). The most popular ACEis present in these combinations include perin-dopril (2) and delapril (7), but the effectiveness of enalapril maleate (ENA) in combination with IND was also established (8).…”
mentioning
confidence: 99%